(untitled) (Islas, 2026)
Introduction: Every literary text contains underlying cultural traits of the society in which it originates. Embedded within it is a set of meanings, values, and symbols that are conveyed through language, and more specifically through what are known as cultural references. This paper addresses the translation into German of Argentine cultural references drawn from Julio Cortázar’s novel Hopscotch (Rayuela). Methods: Using an inductive–contrastive approach, a corpus of cultural references related to the setting is selected, as these reflect key aspects of Buenos Aires idiosyncrasy and pose a challenge for translators. At a microtextual level, the source text and its German translation are compared and analyzed. Results: The analysis shows that, among the four categories of setting-related cultural references identified and examined, references to historical and cultural personalities present the greatest difficulty in translation. Most of these references are transcribed without any form of amplification, which results in the loss of their intended function within the text. A tendency towards domestication in the translation is therefore observed. Conclusions: The study highlights the difficulties involved in translating terms that are closely tied to a specific culture in general, and to Buenos Aires culture in particular. The use of pragmatic explicitation or compensation techniques is proposed as a means of bringing the text closer to the target audience and facilitating a contextualized understanding of the relevance of the setting in which the novel unfolds.